Prevalence of and rationale for antimicrobial prescription during ambulatory care visits in Japan: a prospective, multicentre, cross-sectional study - Junpei Komagamine; Masaki Kobayashi; Takahiro Mori (BMJ Open)
Objective To determine the rate of outpatient antimicrobial use and the rationale for antimicrobial prescription.Design A prospective, multicentre, cross-sectional study.Setting Ambulatory care settings at community general hospitals.Participants A total of 1972 consecutive ambulatory visits by 1952 patients were included from 2 February 2020 to 13 February 2020. Visits resulting in hospital admission and regularly scheduled visits were excluded.Main outcome measures The primary outcome was the proportion of ambulatory visits resulting in antimicrobial drug prescriptions. The secondary outcomes were the reasons for antimicrobial drug prescription and the proportion of unnecessary antimicrobial prescriptions among all antimicrobial drugs used for treatment.Results The mean patient age was 53.8 (SD 25.8) years old, and the proportion of women was 52.6%. A total of 162 antimicrobial drugs were prescribed in 153 (7.8%) visits. The most common antimicrobial drugs were penicillins (n=48, 29.6%), followed by third-generation cephalosporins (n=35, 21.6%) and quinolones (n=20, 12.4%). Among all the antimicrobial drugs prescribed, 125 (77.2%), 18 (11.1%) and 11 (6.8%) were used for infection treatment, wound prophylaxis and surgical prophylaxis, respectively. Of the 125 antimicrobial drugs used for infection treatment, 60 (48.0%) were judged to be unnecessary.Conclusions One in every 13 ambulatory visits resulted in antimicrobial use in Japan. Three-fourths of the prescribed antimicrobial drugs were used for infection treatment, but approximately half of those drugs may have been unnecessary. Further efforts to reduce unnecessary antimicrobial drug use are needed.Trial registration number UMIN000039360.